Dynamics of capillary blood flow responses to acute local changes in oxygen and carbon dioxide concentrations - Russell McEvoy, Gaylene M.; Wells, Brenda N.; Kiley, Meghan E.; Kaur, Kanika K.; Fraser, Graham M. (Frontiers in Physiology, 2022)
Objectives: We aimed to quantify the magnitude and time transients of capillary blood flow responses to acute changes in local oxygen concentration ([O2]), and carbon dioxide concentration ([CO2]) in skeletal muscle. Additionally, we sought to quantify the combined response to both low [O2] and high [CO2] to mimic muscle microenvironment changes at the onset of exercise. Methods: 13 Sprague Dawley rats were anaesthetized, mechanically ventilated, and instrumented with indwelling catheters for systemic monitoring . The extensor digitorum longus muscle was blunt dissected, and reflected over a micro-fluidic gas exchange chamber in the stage of an inverted microscope. Four O2 challenges, four CO2 challenges, and a combined low O2 (7-2%) and high CO2 (5-10%) challenges were delivered to the surface with simultaneous visualization of capillary blood flow responses. Recordings were made for each challenge over a 1-minute baseline period followed by a 2-minute step change. The combined challenge employed a 1-minute [O2] challenge followed by a 2-minute change in [CO2]. Mean data for each sequence were fit using least-squared non-linear exponential models to determine the dynamics of each response. Results: 7-2% [O2] challenges decreased capillary RBC saturation within 2s following the step change (46.53±19.56% vs 48.51±19.02%, p<0.0001, 𝜏=1.44s), increased RBC velocity within 3s (228.53±190.39 μm/s vs 235.74±193.52 μm/s, p<0.0003, 𝜏=35.54s) with a 52% peak increase by the end of the challenge, hematocrit and supply rate show similar dynamics. 5-10% [CO2] challenges increased RBC velocity within 2s following the step change (273.40 ± 218.06 µm/s vs 276.75 ± 215.94 µm/s , p=0.007, 𝜏=79.34s), with a 58% peak increase by the end of the challenge, supply rate and hematocrit show similar dynamics. Combined [O2] and [CO2] challenges resulted in additive responses to all microvascular hemodynamic measures with a 103% peak velocity increase by the end of the collection period. Data for mean responses and exponential fitting parameters are reported for all challenges. Conclusion: Microvascular level changes in muscle [O2] and [CO2] provoked capillary hemodynamic responses with differing time transients. Simulating exercise via combined [O2] and [CO2] challenges demonstrated the independent and additive nature of local blood flow responses to these agents.